ANALISIS PERBANDINGAN METODE MENGHAFAL Al-QUR’AN PADA SANTRI PUTRI (Studi Pesantren Darussalam Dan Pesantren Harsallakum Kota Bengkulu) - Apriani, Ria; Khoiri, Qolbi; Delta Fitrianah, Rossi (Yayasan Darussalam Bengkulu, 2020)
The main problem of this research is how the method of students in memorizing the Qur'an. By looking at the condition of female students not only memorizing the Qur'an in the dormitory, they also have to memorize subjects at school. The research entitled